The effectiveness of ICT-enhanced teaching mode using activity theory on raising class interaction and satisfaction in an engineering course - Dai, Zhicheng; Xiong, Junxia; Zhao, Liang; He, Xiuling (Interactive learning environments, 2024)
Activity theory is of great importance in emphasizing the role of community and intermediary tools in the subject's internalization activities. From the perspective of activity theory, via systematically and comprehensively exploring kinds of different interactions between various elements (e.g. subject, community and tools) in classroom teaching, this study constructed a framework based on ICT-enhanced activity system, and proposed a teaching mode using the constructed framework. To verify its effectiveness in improving classroom interaction and satisfaction, the proposed teaching mode is applied to an engineering course. The experimental results showed that the proposed teaching mode can not only effectively combine theoretical learning with practical application, but also raise students' classroom interaction and satisfaction through rich teaching activities (including such as competitive answering, topic discussion and achievement sharing, etc.). As demonstrated in our experiment, compared with the traditional teaching modes, (i) 83.8% of the participants were more satisfied with the proposed mode, and 70.3% of them preferred that this mode could be maintained in the future teaching; (ii) better instructional design of engineering courses with the accompanying more satisfactions can be gained using the proposed teaching mode. Theoretical and practical contributions to the integration of ICT with engineering courses are offered.